2013
DOI: 10.1016/j.breast.2012.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Association between common risk factors and molecular subtypes in breast cancer patients

Abstract: Reproductive and hormonal characteristics (breastfeeding, parity, age at first full-term birth, hormone replacement therapy) were associated with luminal subtype, compared to non-luminal breast cancer, as consistent with previous studies. Obesity and overweight increased the risk of triple negative subtype, particularly in premenopausal women. Older age and use of hormone replacement therapy were related to the risk of HER-2 overexpressing breast cancer. Our data suggest a significant heterogeneity in associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 33 publications
8
97
0
3
Order By: Relevance
“…Several studies conducted to evaluate the effect of BMI at time of diagnostic on histopathological features concluded that obese postmenopausal women develop more frequently ER/PR positive tumors (Biglia et al, 2013). However, others studies showed that obesity and overweight increases the risk of developing triple negative BC subtype, particularly for premenopausal women (Turkoz et al, 2013). Our results revealed that there is an association between BMI and ER-PR-Her2+ tumor subtype.…”
Section: Discussionsupporting
confidence: 43%
“…Several studies conducted to evaluate the effect of BMI at time of diagnostic on histopathological features concluded that obese postmenopausal women develop more frequently ER/PR positive tumors (Biglia et al, 2013). However, others studies showed that obesity and overweight increases the risk of developing triple negative BC subtype, particularly for premenopausal women (Turkoz et al, 2013). Our results revealed that there is an association between BMI and ER-PR-Her2+ tumor subtype.…”
Section: Discussionsupporting
confidence: 43%
“…14,26 Though there is no significant correlation between family history and different breast cancer subtypes but a study reported approximately 28% TNBC patients with family history being highest among all subtypes. 27 TNBC is repeatedly found to occur in premenopausal women. Early menarche, young age at first childbirth, increased parity, oral contraceptives, obesity these are some common risk factors for TNBC in general.…”
Section: Tnbc Risk Factors For Bangladeshi Womenmentioning
confidence: 99%
“…Although the molecular differences between these subtypes have been described in the literature, there is extensive heterogeneity in the distribution of molecular subtypes 44,60,61 and their causes around the world 62 . Further research is necessary to determine if these differences are due to tumor biology or rather to poor pre-analytic management of the samples, including differences in fixation times and improper interpretation 63,64 .…”
Section: Tumor Biology Heterogeneity Concernsmentioning
confidence: 99%